Using Internet resources and e-learning modalities for training learners in Nutrition for people living with HIV and AIDS in South Africa - Cronje, Johannes Christoffel (University of Pretoria, 2013)
Thesis (DPhil (Information Science))--University of Pretoria, 2006.